IMPACT OF OBESITY ON DEMENTIA: FREE LIFE EXPECTANCIES IN OLDER AUSTRALIAN WOMEN - Gardiner, P. (Innov Aging, 2017)
A number of studies have calculated active or cognitive impairment-free life expectancies but there are limited data on years that people will live with dementia though this is crucial for policy development and service planning. Given that a cure for dementia remains elusive, it is important to assess the impact of potential risk factors, one of which is obesity. Women born in 1921–26 from the Australian Longitudinal Study of Women’s Health were surveyed every three years from 1996 until 2011. Body mass index was calculated at baseline and dementia was identified from the self-report surveys and linked administrative datasets. Using multistate life tables, we examined the impact of obesity on life expectancy and dementia-free life expectancy. We found that obese women had lower life expectancy than women who were not obese though these differences were non-significant. Additionally obesity appeared to have little impact on years lived with or without dementia.